Seguridad ciudadana y los sistemas de videovigilancia. Límites, garantías y regulación (2016)
New technologies have produced unexpected changes and has raised countless challengesto the law. One of them is the video surveillance raises aimed, among manyothers, is to provide greater security for citizens. The use of these systems by the Forcesof Security as a tool to prevent disturbances of public safety in public places raisedmany questions, especially the violation that the use of such systems can give rise tothe right to privacy broad sense. To legitimize their use and prevent interference ofpublic power produced in the "right to life" of people, it was approved in Spain theso-called law of video surveillance legal text that constitutes the regulatory frameworkapplicable to the use of recording systems images and sounds by the Security Forcesin fulfilling the tasks entrusted by the Spanish Constitution concerning the protectionof the free exercise of rights and freedoms. All this in order to protect public safety.